Factors Related To The Occurrence Of Typhoid At Bhayangkara Polda Hospilat, Bengkulu In 2024 - Gustian, Tedi; Wulandari, Wulandari; Darmawansyah, Darmawansyah; Suyanto, Jipri; Surahman, Fery (Journal Hygeia Public Health, 2023)
Intoduction: Typhoid is an acute intestinal infectious disease characterized by symptoms such as abdominal pain, skin rashes, and fever. The WHO estimates the global burden of typhoid fever at 11-20 million cases per year. In Indonesia, the incidence of typhoid fever is about 350-810 cases per 100,000 population. According to the Bengkulu City Health Office, there were 456 cases of typhoid in 2022. At Bhayangkara Hospital Polda Bengkulu, there were 355 cases of typhoid (typhoid fever) in 2022. The purpose of this study is to identify the factors associated with the incidence of typhoid at Bhayangkara Polda Hospital, Bengkulu in 2024. Method: This research is analytical with a cross-sectional study design. The population in this study consists of all patients visiting Bhayangkara Polda Hospital, Bengkulu over the last 3 months, specifically December 2023, January 2024, and February 2024, totaling 8,844 people. The sampling technique used in this study is accidental sampling, with a sample size of 38. Result and Discussion: The results of this study indicate a significant relationship between age and the incidence of typhoid at Bhayangkara Hospital Polda Bengkulu in 2024, with a p-value of 0.009. There is also a relationship between attitude and the incidence of typhoid, with a p-value of 0.019. Furthermore, there is a relationship between knowledge and the incidence of typhoid, with a p-value of 0.001. Conclusion: The recommendation of this study is that the results can enrich the scientific knowledge for researchers and serve as reading material for future research in analyzing factors related to the incidence of typhoid fever at Bhayangkara Polda Hospital, Bengkulu in 2024